Development of an Evidence-Based Tool to Assess the Relative Vulnerability of Different Communities to Tuberculosis - Isworo, Slamet; Handayani, Sri; Hinchcliff, Reece; Hasibuan, Zainal Arifin (Kesmas, 2023)
Identifying specific tuberculosis (TB) vulnerabilities in populations based on their geographical, demographic, and epidemiological characteristics is anessential yet challenging requirement to help reduce and eliminate TB. Assessment tools that can accurately quantify the risks associated with key factorscould be used to measure TB vulnerability efficiently and indicate the most appropriate range of interventions. This study aimed to develop TB vulnerability assessment tools based on a TB vulnerability assessment conceptual framework developed with Leximancer. Three steps to produce the tools were facetanalysis, interpreting the facet to create a list of questions, and expert judgment to confirm the suitability of the questionnaire. The “everything is data” principlewas used to identify the data sources and build the tools. The data came from multiple primary data sources, with a questionnaire survey and observational form, and secondary data from various governmental statistical departments in Indonesia to collect data related to demography, health indicators, climate,temperature, and air quality. These tools will be optimized at scale next year to evaluate their utility for prioritizing and prescribing health system responses to TB in different communities in Central Java Province.